STRATEGI DIGITAL MARKETING UNTUK PRODUK B2B: STUDI KASUS PEMASARAN PRODUK TURUNAN DI PT PUPUK KUJANG - Dzakiya Rahmanita; Reminta Lumban Batu (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
Digital transformation has changed Business to Business marketing, including in the petrochemical industry. This research analyzes the implementation of derivative product digital marketing strategies at PT Pupuk Kujang through Systematic Literature Review (SLR) from ten selected journals. As a result, the use of digital platforms, especially company websites, increases operational efficiency and reduces customer acquisition costs. The website functions as the main channel for product information, technical specifications, and transactions with B2B customers. Digital technology helps simplify marketing, increase visibility, and expand the market. The three key success factors are the integration of technology with products, local market contextualization, and the development of an integrated security model. The main challenge is to balance digital accessibility with strict security protocols. This research contributes to the development of a digital marketing strategy framework that can be adapted by similar companies in Indonesia.